The Effect of Melinjo (Gnetum gnemon L.) Leaves and Melinjo Peel Extracts on Induced-Hyperuricemia Male Rats Model - Nia K Sari; Andreanus A Soemardji; Irda Fidrianny (Journal of Medicine and Health, 2019)
Hyperuricemia is condition which blood uric acid levels increase, in men are greater than 7 mg/dL and in women over 6 mg/dL. In Indonesia the prevalence of hyperuricemia was 32% in people under 34 years and increases every year. Beside an emping from melinjo seed there is Indonesian meals made from mixture of seed, peel and leaves of melinjo, namely as sayur asem. Consumption a lot of emping can induced hyperuricemia. This study aims to assess the effect of melinjo leaves and peel extracts to reduce uric acid levels on melinjo seed hyperuricemia male rats model. Methods: Induction was performed by giving high purine diet, melinjo seed crude drug (emping) 4.5 g/kg bw. Ethanol extracts of melinjo leaves and melinjo peel were administered in 3 doses. Results: Ethanol leaves extract of melinjo (Gnetum gnemon L.) 36 mg/kg bw could decrease uric acid levels up to 61.04%, while ethanol peel extract of melinjo 13 mg/kg bw can decrease uric acid levels up to 31.25%. Conclusions: Melinjo seed crude drug (emping) could increase the bloods uric acid level in rats up to 4.65 mg/dL. Ethanol leaves and peel extracts of melinjo could decrease uric acid blood levels in hyperuricemia rats. Keywords : Gnetum gnemon L., seed, leaves, peel, antihyperuricemia